A participação na gestão da escola a partir das práticas estudantis durante as ocupações escolares no ano de 2015 em São Paulo - Laranja, Mirza Rosas Augusto (2023)
This study had the objective to study the participation of high school students in an important historical moment for public education in the state of São Paulo, 2015- 2016, in the midst of the democratic crisis that had intensified in the country in that period. In such context, the study found, from concrete actions of high school students, how the management processes that develop in school are linked to student participation. The importance of this study lies in deepening the knowledge about a phenomenon in which high school students, sometimes discredited about their interest in taking part in the school, or even in their ability to articulate themselves in an organizational way, autonomously recreated the school space and implemented a management model that predicts the education they advocate. The qualitative approach used several strategies: bibliographic research, mapping of the legal framework, analysis of audiovisual materials, and interviews with educators, managers, and 13 young people of diverse backgrounds in the school and, at the time, students of the network of state public education. The theoretical references bring together authors dedicated to youth contemporaries and their social and political participation and the relations of young people with the school. The research identifies daily practices during the occupations of São Paulo in 2015, related to school management and with direct implications for the participation of students, such as sociability among peers, digital communication, appropriation of school spaces, curricular choices and forms of participation, decisionmaking, and representation, aligned with a conception of democracy. It also analyzes student participation through the political-institutional collegiates proposed by schools, student unions, and school councils, going through the normative framework that sustains them and discussing the timid performance of these collegiates during the student movement of 2015. In addition, the research inserts itself in the discussion of the collective construction of the Pedagogical Political Project and the relationships that students establish with teachers and school management. Finally, it discusses two social and political milestones that occurred after the occupations: the Democratic Management Project of the Secretary of Education of the State of São Paulo (2016- 2017), and the School Without Party Movement. The findings show that school management is linked to the participation of students in school contexts, both in formal instances and in everyday school life. Free socialization, the use of digital informational and communication resources, the social and collective appropriation of space, and curricular choices involving pertinent knowledge and forms are practical fundamentals of youth participation. The findings show that measured institutionalized participatory practices should be reviewed in the light of organizational flexibility, autonomy, representativeness, decentralization of information, and power, which are characteristics present in the way students organized themselves during the São Paulo occupations in 2015